2022
DOI: 10.3390/math10132205
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Bee Colony Algorithm for Static and Dynamic Capacitated Arc Routing Problems

Abstract: The Capacitated Arc Routing Problem (CARP) is a combinatorial optimization problem, which requires the identification of such route plans on a given graph to a number of vehicles that generates the least total cost. The Dynamic CARP (DCARP) is a variation of the CARP that considers dynamic changes in the problem. The Artificial Bee Colony (ABC) algorithm is an evolutionary optimization algorithm that was proven to be able to provide better performance than many other evolutionary algorithms, but it was not use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Complexity analysis of the ABC optimization algorithm has been done in many studies. Nagy et al reported the ABC algorithm as O(n + log n) in their study [42]. Since the ABC algorithm used is the classical ABC algorithm, the complexity value presented in previous studies is also valid here.…”
Section: Adaptation Of Artificial Bee Colony For Ann Trainingmentioning
confidence: 68%
“…Complexity analysis of the ABC optimization algorithm has been done in many studies. Nagy et al reported the ABC algorithm as O(n + log n) in their study [42]. Since the ABC algorithm used is the classical ABC algorithm, the complexity value presented in previous studies is also valid here.…”
Section: Adaptation Of Artificial Bee Colony For Ann Trainingmentioning
confidence: 68%
“…With the development of intelligence optimization methods, variable neighborhood search [17] , genetic algorithm [18] , ant colony optimization [19] , and artificial bee colony algorithm (ABC) [20] have been employed to achieve the optimal routing scheme within acceptable computational time. Among them, artificial bee colony algorithm inspired by bee colony behavior has simpler structure with few parameters and thus has been widely applied in solving combinatorial optimization problems, such as traveling salesman problem [21] , arc routing problem [22] , and vehicle routing problem [23,24] . Although many problem-specific operators have been designed to enhance the ability of exploration and exploitation for ABC, their limitations will be exposed on solving other problems due to no free lunch theorems [25] .…”
Section: Introductionmentioning
confidence: 99%